The Effectiveness of Using the Tribunnews Instagram Account in Developing News Text Writing - Wirahyuni, Kadek; Nengah Martha, I (Educationist: Journal of Educational and Cultural Studies, 2022)
Technology that is increasingly developing brings a lot of progress in life, including supporting the world of education. Unfortunately, there are still many teachers who have not taken advantage of technological advances. For example, the Indonesian VIII B teacher at SMP 17 Agustus – 1 Muncar, uses monotonous learning media. This study aims to test the media for learning the Instagram Tribunnews account in learning news texts for class VIII students. This study uses an experimental method, with a One-Group Pretest-Posttest Design model. The sample used in this study was class VIII SMP 17 Agustus – 1 Muncar. The results of this study indicate that learning news texts with Instagram Tribunnews has several stages, namely: pretest, experiment, and post-test. The ability to write news texts before using the Tribunnews Instagram account obtained an average value of 53.33 which was included in the less category. After using Tribunnews Instagram media, the average score rose to 86.25 in the excellent category. Therefore, there is an effect on the use of the Tribunnews Instagram account on the ability to write news texts by VIII grade students of SMP 17 Agustus 1945 – 1 Muncar.